Hydrophobic nano oxide solid electrolyte as well as preparation method and application thereof

Through airflow crushing and molecular bonding technology, the problem of excessive moisture content of oxide solid electrolytes after mechanical crushing is solved, and low-water, easy-to-disperse hydrophobic nanooxide solid electrolytes are prepared, which improves the high-temperature performance of lithium-ion batteries and Cyclic stability.

CN119133582APending Publication Date: 2024-12-13LIONGO (CHANGZHOU) NEW ENERGY CO LTD

Patent Information

Application Number
CN202411329987.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The high-energy active sites formed by the oxide solid electrolyte in existing semi-solid lithium-ion batteries during mechanical crushing lead to a large number of polar groups on the surface, which are easy to combine with solvents or water molecules in the air, forming high-water solid electrolytes, affecting Battery performance.

Method used

The gas stream crushing method is used to crush the mixture of gaseous halogenated hydrocarbons and inert gas. The halogenated hydrocarbons are molecularly bonded to the groups on the surface of the powder to form a hydrophobic layer, reducing the moisture content of the solid electrolyte, and dry nanometers The chemical treatment avoids agglomeration and improves the dispersion and fluidity of the powder.

Benefits of technology

The preparation of low-moisture solid electrolyte is achieved, the high-temperature performance and cycle stability of the battery are improved, the moisture content and drying temperature of the battery are reduced, and the hydrophobicity and dispersion of the solid electrolyte are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly relates to a hydrophobic nano oxide solid electrolyte as well as a preparation method and application thereof. Compared with the prior art, the method has the advantages that an airflow crushing method is adopted, a halogenated hydrocarbon and inert gas mixed gas source is used as jet airflow, and secondary agglomerated powder is depolymerized again, so that the purposes of nanocrystallization and hydrophobicity are achieved; meanwhile, the halogenated hydrocarbon is subjected to molecular bonding with groups on the surface of the powder in the process, hydrophobic M-O-R (M represents a metal element and R represents alkyl) is formed on the surface, and finally the low-moisture solid electrolyte is obtained; and the nano solid electrolyte powder subjected to hydrophobic treatment is less in agglomeration, easy to disperse, good in powder fluidity, low in water content and low in water absorption in air and water, so that a nano solid electrolyte coating diaphragm prepared from the nano solid electrolyte powder has the advantages of low water content, low drying temperature, good battery high-temperature performance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a hydrophobic nano oxide solid electrolyte and a preparation method and application thereof. Background Art

[0002] Lithium-ion battery technology is developing along the technical route from liquid to all-solid state. The main reason for this development trend is that the energy density and safety of batteries need to be greatly improved. However, all-solid-state battery technology still faces many technical problems, such as the low ion conductivity of oxide solid electrolytes and the sensitivity of sulfide solid electrolytes to air.

[0003] Semi-solid-state battery technology is a technical means to improve battery safety by introducing some solid electrolytes to reduce the amount of electrolyte used on the basis of traditional liquid battery technology. Semi-solid-state battery technology combines the excellent thermal stability of oxide solid electrolytes with the high ionic conductivity of liquid batteries. The size of oxide solid electrolytes used in semi-solid batteries needs to be submicron or nanometer to ensure good dispersion and uniformity in the battery. Mechanical crushing such as wet ball milling and sand milling of powder particles is the main way to prepare nano-scale oxide solid electrolytes. However, due to the breakage of chemical bonds during the mechanical crushing process, a large number of active sites will be formed on the fresh interface of the particles, resulting in a large number of polar groups such as Li-O, Al-O, and Ti-O on the surface. These high-energy active sites will combine with water molecules in the solvent or air to form a solid electrolyte with a high water content. High-water solid electrolytes will seriously reduce the performance of the battery when used for positive electrode blending and diaphragm coating, causing adverse effects such as high-temperature battery attenuation and cycle degradation.

[0004] A common treatment method is to perform hydrophobic treatment on the surface of the solid electrolyte. The Chinese patent with publication number CN111342117A discloses a surface treatment method for spraying a super-hydrophobic material on a solid electrolyte, wherein the super-hydrophobic material is a mixture of nano cobalt oxide, trifluoroethanesulfonic acid, and PVA aqueous solution, and heptane is added as a solvent for heating and stirring to dissolve, to obtain a super-hydrophobic pretreatment solution, which is sprayed on the surface of the solid electrolyte. The Chinese patent with publication number CN115117436A uses a silane coupling agent to coat the solid electrolyte to obtain a solid electrolyte coated with a surface hydrophobic material. However, the existing method still has the following disadvantages: 1) The surface coating technology causes the surface of the solid electrolyte to be covered with an inert material, which affects the ion transport of the solid electrolyte; 2) After the nano-sized solid electrolyte is coated by the wet method, it also needs to be dried and a second ball milling process, which causes the coating layer of the nanoparticles to be destroyed, affecting the hydrophobic effect of the solid electrolyte; 3) The ball milling process of the dried powder will also cause the solid electrolyte to produce a new hydrophilic interface, resulting in an increase in the water absorption of the solid electrolyte. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a hydrophobic nano-oxide solid electrolyte with less agglomeration and easy dispersion, and a preparation method and application thereof.

[0006] The present invention provides a method for preparing a hydrophobic nano-oxide solid electrolyte, comprising the following steps:

[0007] S1) dispersing coarse oxide solid electrolyte powder in a solvent and grinding it to obtain a slurry;

[0008] S2) drying the slurry to obtain a powder;

[0009] S3) performing air flow pulverization on the powder to obtain a hydrophobic nano oxide solid electrolyte; the gas source of the air flow pulverization is a mixture of gaseous halogenated hydrocarbons and inert gases.

[0010] Preferably, the volume concentration of the gaseous halogenated hydrocarbon in the mixed gas is 0.5% to 50%; the halogenated hydrocarbon is selected from one or more of methyl chloride, ethyl chloride, methyl bromide and ethyl bromide.

[0011] Preferably, the pressure of the mixed gas during the air flow milling is 0.5-2 MPa; the temperature of the mixed gas is 80°C-200°C; the flow rate of the mixed gas is 1-10 m 3 / min.

[0012] Preferably, the oxide solid electrolyte is selected from NASICON type oxide solid electrolyte Li 1+x A x B 2-x (PO4)3 and / or Perovskite-type oxide solid electrolyte Li 3y La 2 / 3-y TiO3; wherein A is selected from one or more of Al, La, In, Cr, Ga, Fe, Sc, Lu and Y; B is selected from one or more of Ti, Ge, Zr, Hf and Sn; 0≤x≤0.5; 0<y≤2 / 3.

[0013] Preferably, in the step S1), the oxide solid electrolyte coarse powder is first dispersed in a solvent to obtain a dispersion, and then the dispersion is ground; the mass concentration of the oxide solid electrolyte coarse powder in the dispersion is 10% to 50%; the dispersion speed is 200 to 700 rpm; the dispersion time is 5 to 60 min; and the solvent is selected from deionized water.

[0014] Preferably, the particle size of the oxide solid electrolyte coarse powder in step S1) is 1-100 μm;

[0015] The grinding speed is 1000-3000 rpm;

[0016] The particle size D50 of the slurry is 100-800 nm.

[0017] Preferably, the drying method in step S2) is selected from one or more of spray drying, vacuum drying, forced air drying and flash drying; and the moisture content of the powder is less than 30,000 ppm.

[0018] The present invention also provides a hydrophobic nano-oxide solid electrolyte prepared by the above preparation method.

[0019] The present invention also provides a battery, comprising the hydrophobic nano-oxide solid electrolyte prepared by the above preparation method.

[0020] Preferably, the battery includes a solid electrolyte coating diaphragm; the solid electrolyte coating diaphragm includes a diaphragm base membrane and a solid electrolyte layer arranged on the surface of the diaphragm base membrane; the solid electrolyte layer includes the hydrophobic nano-oxide solid electrolyte prepared by the above preparation method.

[0021] The present invention provides a method for preparing a hydrophobic nano oxide solid electrolyte, comprising the following steps: S1) dispersing a coarse oxide solid electrolyte powder in a solvent and grinding it to obtain a slurry; S2) drying the slurry to obtain a powder; S3) airflow pulverizing the powder to obtain a hydrophobic nano oxide solid electrolyte; the gas source of the airflow pulverizing is a mixed gas of gaseous halogenated hydrocarbons and inert gas. Compared with the prior art, the present invention adopts an airflow pulverizing method, and uses a mixed gas source of halogenated hydrocarbons and inert gas as a jet gas flow to re-depolymerize the secondary agglomerated powder, thereby achieving the purpose of nano-ization and hydrophobicity; at the same time, since the halogenated hydrocarbons will undergo molecular bonding with the groups on the surface of the powder in this process, a hydrophobic MOR (M represents a metal element, and R represents an alkyl group) is formed on the surface, and finally a low-moisture solid electrolyte is obtained; and the nano solid electrolyte powder after the hydrophobic treatment has less agglomeration, is easy to disperse, has good powder fluidity, low water content, and low water absorption in air and water, and then the nano solid electrolyte coating diaphragm prepared by using it has the advantages of low water content, low drying temperature, and good high-temperature performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is a particle size distribution diagram of the powder obtained in Example 2 of the present invention;

[0023] Figure 2 This is a scanning electron microscope image of the powder obtained in Example 2 of the present invention. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] The invention provides a method for preparing a hydrophobic nano oxide solid electrolyte, comprising the following steps: S1) dispersing coarse oxide solid electrolyte powder in a solvent and grinding it to obtain a slurry; S2) drying the slurry to obtain a powder; S3) air flow pulverizing the powder to obtain a hydrophobic nano oxide solid electrolyte; the gas source of the air flow pulverizing is a mixture of gaseous halogenated hydrocarbons and inert gases.

[0026] In the process of air flow pulverization, the present invention adopts a gaseous halogenated hydrocarbon high-pressure gas source to directly interact with the hydrophilic groups on the surface of the solid electrolyte at high temperature, making the surface of the solid electrolyte hydrophobic, thereby obtaining a solid electrolyte powder with low water content. In addition, the powder is modified in the air flow pulverization stage, and the fresh surface energy generated when the powder collides with the dry gas is high, the reaction with the halogenated hydrocarbon is strong, and the bonding strength is large. In addition, the present invention adopts a dry method to nano-size the powder, and the nano-sized powder does not agglomerate and is easy to disperse.

[0027] The present invention has no particular limitation on the sources of all raw materials, as long as they are commercially available.

[0028] The oxide solid electrolyte coarse powder is dispersed in a solvent and ground to obtain a slurry; the oxide solid electrolyte can be an oxide solid electrolyte well known to those skilled in the art, and there is no special limitation. In the present invention, NASICON-type oxide solid electrolyte Li 1+x A x B 2-x (PO4)3 and / or Perovskite-type oxide solid electrolyte Li 3y La 2 / 3-y TiO3; wherein A is preferably one or more of Al, La, In, Cr, Ga, Fe, Sc, Lu and Y; B is preferably one or more of Ti, Ge, Zr, Hf and Sn; 0≤x≤0.5; 0<y≤2 / 3; in some embodiments provided by the present invention, the oxide solid electrolyte is specifically Li 1.4 Al 0.4 Ti 1.6 (PO4)3 or Li 0.5 La 0.5TiO3; the particle size of the oxide solid electrolyte coarse powder is preferably micron-sized, more preferably 1-100 μm; the solvent can be a solvent well known to those skilled in the art, without any special restrictions, and is preferably deionized water in the present invention; in the present invention, preferably, the micron-sized oxide solid electrolyte coarse powder is first dispersed in a solvent to obtain a dispersion, and then ground; the dispersion speed is preferably 200-700 rpm, more preferably 400-600 rpm, and more preferably 500 rpm; the dispersion time is preferably 5-60 min, more preferably 10-40 min, and more preferably 20-30 min; the mass concentration of the oxide solid electrolyte coarse powder in the dispersion is preferably 10%-50%, more preferably 10%-40%, more preferably 10%-30%, and most preferably 10%-20%; the grinding method can be a method well known to those skilled in the art, without any special restrictions, and is preferably ball milling or sand milling in the present invention, and more preferably sand milling; the grinding speed is preferably 1000-3000 rpm; the grinding time is preferably 5-15 h, more preferably 5~10h, and even more preferably 5~8 h; the grinding is preferably carried out in the presence of a grinding medium; the grinding medium is preferably a zirconia ball; the diameter of the grinding medium is preferably 0.1~1 mm; in some embodiments provided by the present invention, the diameter of the grinding medium is specifically 1 mm, 0.6 mm, 0.8 mm, 0.3 mm or 0.1 mm; the particle size of the slurry (i.e., the particle size of the particles in the slurry) D50 is preferably 100~800 nm; in some embodiments provided by the present invention, the particle size D50 of the slurry is specifically 800nm, 500 nm, 200 nm or 100 nm.

[0029] The slurry is dried to obtain a powder; the drying method is a method well known to those skilled in the art, and there is no particular limitation as long as a low-moisture powder can be obtained. In the present invention, one or more of spray drying, vacuum drying, blast drying and flash drying are preferred; the moisture content of the powder is preferably less than 30,000 ppm.

[0030] The powder is subjected to air flow pulverization to obtain a hydrophobic nano-oxide solid electrolyte; the gas source for the air flow pulverization is a mixture of gaseous halogenated hydrocarbons and inert gases; the halogenated hydrocarbons can be halogenated hydrocarbons well known to those skilled in the art, and there is no special limitation. The number of carbon atoms of the halogenated hydrocarbons in the present invention is preferably 1 to 5, more preferably 1 to 3, and more preferably 1 or 2; the halogen atoms in the halogenated hydrocarbons are preferably bromine or chlorine; in the present invention, most preferably, the halogenated hydrocarbons are one or more of methyl chloride, ethyl chloride, methyl bromide and ethyl bromide; the volume concentration of gaseous halogenated hydrocarbons in the mixed gas is preferably 0.5% to 50%, more preferably 0.9% to 50%; the pressure of the mixed gas during the air flow pulverization is preferably 0.5 to 2 MPa; in some embodiments provided by the present invention, the pressure of the mixed gas during the air flow pulverization is specifically 2 MPa, 1 MPa or 0.5 MPa; the temperature of the mixed gas is preferably 80°C~200°C, more preferably 100°C~200°C; in some embodiments provided by the present invention, the temperature of the mixed gas is specifically 80°C, 120°C, 200°C or 100°C; the flow rate of the mixed gas is preferably 1~10 m 3 / min, more preferably 5~10 m 3 / min, preferably 7~10 m 3 / min, preferably 8~9 m 3 / min, the most preferred is 8.3~8.5 m 3 / min; the powder after airflow crushing is preferably classified to obtain a hydrophobic nano-oxide solid electrolyte; the particle size of the hydrophobic nano-oxide solid electrolyte is preferably 100~800 nm; in some embodiments provided by the present invention, the particle size of the hydrophobic nano-oxide solid electrolyte is specifically 800 nm, 500 nm or 100 nm.

[0031] The present invention adopts a gas flow pulverization method, uses a mixed gas source of halogenated hydrocarbons and inert gases as a jet gas flow, and re-depolymerizes the secondary agglomerated powder, thereby achieving the purpose of nano-ization and hydrophobicity; at the same time, since the halogenated hydrocarbons will undergo molecular bonding with the groups on the surface of the powder during this process, a hydrophobic MOR (M represents a metal element, and R represents an alkyl group) is formed on the surface, and finally a low-moisture solid electrolyte is obtained; and the nano solid electrolyte powder after the hydrophobic treatment is not easy to agglomerate, has good powder fluidity, low water content, and low water absorption in air and water, and thus the nano solid electrolyte coating diaphragm prepared by using the same has the advantages of low water content, low drying temperature, good high-temperature performance of the battery, and the like.

[0032] The present invention also provides a hydrophobic nano-oxide solid electrolyte prepared by the above method; the hydrophobic nano-oxide solid electrolyte comprises a nano-oxide solid electrolyte; an alkyl group is bonded to the surface of the nano-oxide solid electrolyte via a polar group; the carbon atom number of the alkyl group is preferably 1 to 5, more preferably 1 to 3, and even more preferably 1 or 2.

[0033] According to the present invention, the particle size of the hydrophobic nano-oxide solid electrolyte is preferably 100-800 nm; in some embodiments provided by the present invention, the particle size of the hydrophobic nano-oxide solid electrolyte is specifically 800 nm, 500 nm or 100 nm.

[0034] The present invention also provides a battery, comprising the hydrophobic nano-oxide solid electrolyte prepared by the above preparation method.

[0035] According to the present invention, the battery is preferably a lithium-ion battery.

[0036] According to the present invention, the battery includes a solid electrolyte coating diaphragm; the solid electrolyte coating diaphragm includes a diaphragm base film and a solid electrolyte layer arranged on the surface of the diaphragm base film; the solid electrolyte layer includes a hydrophobic nano oxide solid electrolyte prepared by the above preparation method; the diaphragm base film can be a diaphragm base film well known to those skilled in the art, and there is no special restriction. In the present invention, it is preferably a polyethylene base film and / or a polypropylene diaphragm; the thickness of the diaphragm base film is preferably 5~20 μm, more preferably 5~15 μm, and more preferably 9~10 μm; the thickness of the solid electrolyte layer is preferably 0.5~5 μm, more preferably 1~3 μm, and more preferably 2 μm; the mass concentration of the hydrophobic nano oxide solid electrolyte in the solid electrolyte layer is preferably 75%~98%, more preferably 78%~98%, more preferably 80%~95%, more preferably 85%~95%, more preferably 88%~92%, and most preferably 90%.

[0037] According to the present invention, the solid electrolyte coating diaphragm is prepared specifically according to the following method: mixing a hydrophobic nano oxide solid electrolyte, an adhesive, a surface wetting agent and water to obtain a coating slurry; coating the coating slurry on the diaphragm base film, drying, and obtaining a solid electrolyte coating diaphragm; further specifically, firstly dispersing the hydrophobic nano oxide solid electrolyte in water to obtain a dispersion, and then adding an adhesive and a surface wetting agent to mix to obtain a coating slurry; the mass concentration of the hydrophobic nano oxide solid electrolyte in the dispersion is preferably 20% to 40%, more preferably 25% to 35%, and more preferably 30%; the adhesive can be an aqueous adhesive well known to those skilled in the art, and there is no special restriction. In the present invention, it is preferably polyacrylic acid and / or polyacrylic acid modified adhesive; the mass concentration of the adhesive in the coating slurry is preferably 1% to 5%, more preferably 2% to 4%, and more preferably 3%; the surface wetting agent can be a surface wetting agent well known to those skilled in the art, and there is no special restriction. In the present invention, it is preferably BYK-LPX 20990; the mass concentration of the surface wetting agent in the coating slurry is preferably 0.1%~0.5%, more preferably 0.2%~0.4%, and more preferably 0.2%~0.3%; the drying temperature is preferably 40℃~60℃, more preferably 50℃.

[0038] In order to further illustrate the present invention, a hydrophobic nano-oxide solid electrolyte provided by the present invention and its preparation method and application are described in detail below in conjunction with embodiments.

[0039] The reagents used in the following examples are all commercially available; the polyacrylic acid adhesive used in the examples is GR-506 (Hunan Gaorui); the model of the PE base film used is ND9 (Shanghai Enjie).

[0040] Example 1

[0041] 1.1 10 kg Li 1.4 Al 0 .4 Ti 1.6 The (PO4)3 coarse powder and 40 kg of deionized water were mixed and dispersed in a high-speed disperser at a stirring speed of 500 rpm for 20 min to obtain a dispersion.

[0042] 1.2 The above dispersion was put into a sand mill, and then sand-milled with a 1 mm zirconium ball for 5 h until the D50 particle size was 800 nm to obtain a slurry.

[0043] 1.3 The slurry is dried into a low-moisture powder by spray drying, and the moisture content is less than 30,000 ppm.

[0044] 1.4 The powder obtained by spray drying was sent to the air flow mill, and the ratio of methyl chloride and N2 gas was controlled to be 100:100 by the mass flow meter, and the gas flow rate was 8.5 m 3 / min, the pressure is 2 MPa, the mixed gas is used as the gas source for air flow grinding, and the heater of the gas source is adjusted to make the gas temperature 80℃. In the grinding chamber, the high-pressure mixed gas carries the powder through the supersonic nozzle to collide with each other. And in the collision process, the methyl chloride gas adsorbs on the surface of LATP, so that the surface of the powder produces a hydrophobic state. The powder in the grinding chamber is screened out by the classification theory to obtain LATP powder with a qualified particle size, and the particle size of the powder is controlled at about 800 nm.

[0045] Example 2

[0046] 2.1 10 kg Li 1.4 Al 0.4 Ti 1.6 The (PO4)3 coarse powder and 90 kg of deionized water were mixed and dispersed in a high-speed disperser at a stirring speed of 500 rpm for 20 min to obtain a dispersion.

[0047] 2.2 The above dispersion was put into a sand mill, and then sand-milled with a 0.6 mm zirconium ball for 8 h until the D50 particle size was 500 nm to obtain a slurry.

[0048] 2.3 The slurry is dried into a low-moisture powder by spray drying, and the moisture content is less than 30,000 ppm.

[0049] 2.4 The powder obtained by spray drying was sent to the air flow mill, and the ratio of methyl chloride and N2 gas was controlled by the mass flow meter to be 1:100, and the gas flow rate was 8.5 m 3 / min, the pressure is 1 MPa, the mixed gas is used as the gas source for air flow grinding, and the heater of the gas source is adjusted to make the gas temperature 120℃. In the grinding chamber, the high-pressure mixed gas carries the powder through the supersonic nozzle to collide with each other. And in the collision process, the methyl chloride gas adsorbs on the surface of LATP, so that the surface of the powder becomes hydrophobic. The powder in the grinding chamber is screened out by the classification theory to obtain LATP powder with qualified particle size, and the particle size of the powder is controlled at about 500 nm. The powder particle size distribution diagram is shown in Figure 1 The powder obtained in Example 2 was analyzed using a scanning electron microscope, and its surface morphology was obtained as follows: Figure 2 shown.

[0050] Example 3

[0051] 3.1 10 kg Li 1.4 Al 0.4 Ti 1.6The (PO4)3 coarse powder and 40 kg of deionized water were mixed and dispersed in a high-speed disperser at a stirring speed of 500 rpm for 20 min to obtain a dispersion.

[0052] 3.2 The above dispersion was put into a sand mill, and then sand-milled with a 0.6 mm zirconium ball for 10 h until the D50 particle size was 100 nm to obtain a slurry.

[0053] 3.3 The slurry is dried into a low-moisture powder by spray drying, and the moisture content is less than 30,000 ppm.

[0054] 3.4 The powder obtained by spray drying was sent to the air flow mill, and the ratio of methyl chloride and N2 gas was controlled to be 100:100 by the mass flow meter, and the gas flow rate was 8.5 m 3 / min, the pressure is 2 MPa, the mixed gas is used as the gas source for air flow crushing, and the heater of the gas source is adjusted to make the gas temperature 200℃. In the crushing chamber, the high-pressure mixed gas carries the powder through the supersonic nozzle to collide with each other. And in the collision process, the methyl chloride gas adsorbs on the surface of LATP, so that the surface of the powder produces a hydrophobic state. The powder in the crushing chamber is screened out by the classification theory to obtain LATP powder with a qualified particle size, and the particle size of the powder is controlled at about 100 nm.

[0055] Example 4

[0056] 4.1 10 kg Li 0.5 La 0.5 The TiO3 coarse powder and 40 kg of deionized water were mixed and dispersed in a high-speed disperser at a stirring speed of 500 rpm for 20 min to obtain a dispersion.

[0057] 4.2 The above dispersion was put into a sand mill and then sand-milled with a 0.8 mm zirconium ball for 5 h until the D50 particle size was 800 nm.

[0058] 4.3 The above dispersion is dried into a low-moisture powder by spray drying, and the moisture content is less than 30,000 ppm.

[0059] 4.4 The powder obtained by spray drying was sent to the air flow mill, and the ratio of methyl chloride and N2 gas was controlled to be 100:100 by the mass flow meter, and the gas flow rate was 8.5 m 3 / min, the pressure is 2Mpa, the mixed gas is used as the gas source for air flow crushing, and the heater of the gas source is adjusted to make the gas temperature 80℃. In the crushing chamber, the high-pressure mixed gas carries the powder through the supersonic nozzle to collide with each other. And in the collision process, the methyl chloride gas adsorbs on the surface of LLTO, so that the surface of the powder produces a hydrophobic state. The powder in the crushing chamber is screened out by the classification theory to obtain LLTO powder with a qualified particle size, and the particle size of the powder is controlled at about 800 nm.

[0060] Example 5

[0061] 5.1 10 kg Li 0.5 La 0.5 TiO3 coarse powder and 40 kg of deionized water were mixed and dispersed in a high-speed disperser at a stirring speed of 500 rpm for 20 min to obtain a dispersion.

[0062] 5.2 The above dispersion was put into a sand mill, and then sand-milled with a 0.6 mm zirconium ball for 8 h until the D50 particle size was 500 nm to obtain a slurry.

[0063] 5.3 The slurry is dried into a low-moisture powder by spray drying, and the moisture content is less than 30,000 ppm.

[0064] 5.4 The powder obtained by spray drying was sent to the air flow mill. The ratio of ethyl chloride and N2 gas was controlled by mass flow meter to be 1:100, and the gas flow rate was 8.5 m 3 / min, the pressure is 2 MPa, the mixed gas is used as the gas source for air flow crushing, and the heater of the gas source is adjusted to make the gas temperature 100℃. In the crushing chamber, the high-pressure mixed gas carries the powder through the supersonic nozzle to collide with each other. And in the collision process, the monochloroethane gas adsorbs on the surface of LLTO, so that the surface of the powder produces a hydrophobic state. The powder in the crushing chamber is screened out by the classification theory to obtain LLTO powder with a qualified particle size, and the particle size of the powder is controlled at about 500 nm.

[0065] Example 6

[0066] 6.1 10 kg Li 0.5 La 0.5 The TiO3 coarse powder and 40 kg of deionized water were mixed and dispersed in a high-speed disperser at a stirring speed of 500 rpm for 20 min to obtain a dispersion.

[0067] 6.2 The above dispersion was put into a sand mill and then sand-milled with a 0.1 mm zirconium ball for 12 h until the D50 particle size was 200 nm.

[0068] 6.3 Dry the above dispersion into low-moisture powder by spray drying, with the moisture content less than 30,000 ppm.

[0069] 6.4 The powder obtained by spray drying was sent to the air flow mill. The ratio of methyl chloride and N2 gas was controlled to be 100:100 by the mass flow meter. The gas flow rate was 8.5 m 3 / min, the pressure is 0.5 MPa. The mixed gas is used as the gas source for air flow grinding, and the heater of the gas source is adjusted to make the gas temperature 200℃. In the grinding chamber, the high-pressure mixed gas carries the powder through the supersonic nozzle to collide with each other. And in the collision process, the methyl chloride gas adsorbs on the surface of LLTO, so that the surface of the powder produces a hydrophobic state. The powder in the grinding chamber is screened out by the classification theory to obtain LLTO powder with a qualified particle size, and the particle size of the powder is controlled at about 200 nm.

[0070] Comparative Example 1

[0071] 1.1 10 kg Li 1.4 Al 0.4 Ti 1.6 The (PO4)3 coarse powder and 40 kg of deionized water were mixed and dispersed in a high-speed disperser at a stirring speed of 500 rpm for 20 min to obtain a dispersion.

[0072] 1.2 The above dispersion was put into a sand mill, and then sand-milled with a 0.6 mm zirconium ball for 8 h until the D50 particle size was 500 nm to obtain a slurry.

[0073] 1.3 The slurry is dried into a low-moisture powder by spray drying, and the moisture content is less than 30,000 ppm.

[0074] 1.4 The powder obtained by spray drying is sent to the air flow mill and compressed air is passed through the air flow rate of 8.5m 3 / min, the pressure is 2 MPa, as the gas source for air flow grinding, and the heater of the gas source is adjusted to make the gas temperature 120℃. In the grinding chamber, the high-pressure mixed gas carries the powder through the supersonic nozzle to collide with each other. The powder in the grinding chamber is screened out by the classification theory to obtain LATP powder with qualified particle size, and the particle size of the powder is controlled at about 500 nm.

[0075] Comparative Example 2

[0076] 2.1 10 kg Li 1.4 Al 0.4 Ti 1.6 The (PO4)3 coarse powder and 40 kg of deionized water were mixed and dispersed in a high-speed disperser at a stirring speed of 500 rpm for 20 min to obtain a dispersion.

[0077] 2.2 The above dispersion was put into a sand mill, and then sand-milled with a 0.6 mm zirconium ball for 5 h until the D50 particle size was 500 nm to obtain a slurry.

[0078] 2.3 The slurry is dried into a low-moisture powder by spray drying, and the moisture content is less than 30,000 ppm.

[0079] 2.4 The powder obtained by spray drying was sent to the air flow mill and N2 was introduced at a gas flow rate of 8.5 m 3 / min, the pressure is 2 MPa, as the gas source for air flow grinding, and the heater of the gas source is adjusted to make the gas temperature 120℃. In the grinding chamber, the high-pressure mixed gas carries the powder through the supersonic nozzle to collide with each other. The powder in the grinding chamber is screened out by the classification theory to obtain LATP powder with qualified particle size, and the particle size of the powder is controlled at about 500 nm.

[0080] Comparative Example 3

[0081] 3.1 10 kg Li 0.5 La 0.5 The TiO3 coarse powder and 40 kg of deionized water were mixed and dispersed in a high-speed disperser at a stirring speed of 500 rpm for 20 min to obtain a dispersion.

[0082] 3.2 The above dispersion was put into a sand mill and then ground with 0.6 mm sand for 8 h until the D50 particle size was 500 nm to obtain a slurry.

[0083] 3.3 The above dispersion is dried into a low-moisture powder by spray drying, and the moisture content is less than 30,000 ppm.

[0084] 3.4 The powder obtained by spray drying was sent to the air flow mill and N2 was introduced at a gas flow rate of 8.5 m 3 / min, the pressure is 2 MPa, as the gas source for air flow grinding, and the heater of the gas source is adjusted to make the gas temperature 120℃. In the grinding chamber, the high-pressure mixed gas carries the powder through the supersonic nozzle to collide with each other. The powder in the grinding chamber is screened out by the classification theory to obtain LLTO powder with qualified particle size, and the particle size of the powder is controlled at about 500 nm.

[0085] The solid electrolyte materials prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were dispersed in water to obtain a dispersion having a mass concentration of 30%, 3% of an aqueous binder (polyacrylic binder) and 0.2% of a surface wetting agent BYK-LPX 20990 were added to the dispersion to obtain coating slurries, respectively; the coating slurry was coated on a PE base film (thickness of 9 μm) by a casting method, and dried in a drying oven at 50° C. for 20 min to obtain a composite diaphragm having a coating thickness of 2 μm, namely, a solid electrolyte coating diaphragm.

[0086] The solid electrolyte coated diaphragm was assembled in the NCM811-graphite battery, with the coating of the coated diaphragm facing the positive side of the battery, and the battery was tested at a high temperature cycle at 60°C, and the results are shown in Table 1. The diaphragm moisture detection method was tested in accordance with T / CPPIA 10-2021, with the test temperature set to 150°C and the test time 10 min. The battery storage volume change was tested by the drainage method to test the volume change of the battery before and after storage at 60°C for 7. The 60°C high temperature cycle test used the Xinwei battery test system to test the capacity retention rate of the battery under 1C charge and 1C discharge cycles.

[0087] Table 1 Powder and diaphragm moisture test results and battery cycle performance

[0088]

[0089] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a hydrophobic nano-oxide solid electrolyte, characterized in that: The following steps are involved: S1) dispersing coarse oxide solid electrolyte powder in a solvent and grinding it to obtain a slurry; S2) drying the slurry to obtain a powder; S3) performing air flow pulverization on the powder to obtain a hydrophobic nano oxide solid electrolyte; the gas source of the air flow pulverization is a mixture of gaseous halogenated hydrocarbons and inert gases.

2. The preparation method according to claim 1, characterized in that: The volume concentration of gaseous halogenated hydrocarbons in the mixed gas is 0.5% to 50%; the halogenated hydrocarbons are selected from one or more of methyl chloride, ethyl chloride, methyl bromide and ethyl bromide.

3. The preparation method according to claim 1, characterized in that: The pressure of the mixed gas during the air flow milling is 0.5~2 MPa; the temperature of the mixed gas is 80℃~200℃; the flow rate of the mixed gas is 1~10 m 3 / min.

4. The preparation method according to claim 1, characterized in that: The oxide solid electrolyte is selected from NASICON type oxide solid electrolyte Li 1+x A x B 2-x (PO4)3 and / or Perovskite-type oxide solid electrolyte Li 3y La 2 / 3- y TiO3; wherein A is selected from one or more of Al, La, In, Cr, Ga, Fe, Sc, Lu and Y; B is selected from one or more of Ti, Ge, Zr, Hf and Sn; 0≤x≤0.5; 0<y≤2 / 3.

5. The preparation method according to claim 1, characterized in that: In the step S1), the oxide solid electrolyte coarse powder is first dispersed in a solvent to obtain a dispersion, and then the dispersion is ground; the mass concentration of the oxide solid electrolyte coarse powder in the dispersion is 10% to 50%; the dispersion speed is 200 to 700 rpm; the dispersion time is 5 to 60 minutes; and the solvent is selected from deionized water.

6. The preparation method according to claim 1, characterized in that: The particle size of the oxide solid electrolyte coarse powder in step S1) is 1-100 μm; The grinding speed is 1000-3000 rpm; The particle size D50 of the slurry is 100-800 nm.

7. The preparation method according to claim 1, characterized in that: The drying method in step S2) is selected from one or more of spray drying, vacuum drying, blast drying and flash drying; the moisture content of the powder is less than 30,000 ppm.

8. A hydrophobic nano-oxide solid electrolyte prepared by the preparation method according to any one of claims 1 to 7.

9. A battery, characterized in that: A hydrophobic nano-oxide solid electrolyte prepared by any one of the preparation methods of claims 1 to 7.

10. The battery according to claim 10, characterized in that The battery comprises a solid electrolyte coating diaphragm; the solid electrolyte coating diaphragm comprises a diaphragm base membrane and a solid electrolyte layer arranged on the surface of the diaphragm base membrane; the solid electrolyte layer comprises a hydrophobic nano-oxide solid electrolyte prepared by any one of the preparation methods of claims 1 to 7.

Citation Information

Patent Citations

  • Super-hydrophobic solid electrolyte of lithium-air battery and preparation method thereof

    CN111342117A

  • Method for reducing moisture content of nano ion conductor solid electrolyte and battery

    CN115117436A

Cited By

  • Sulfide solid electrolyte, preparation method thereof and all-solid-state battery

    CN121307166A